ANTIBIOTIC SUSCEPTIBILITY PROFILES OF SELECTED BACTERIA ISOLATED FROM LOCALLY-PREPARED FEMALE APHRODISIACS SOLD IN DUTSE, JIGAWA STATE, NIGERIA - Ibrahim, Yusuf Musa; Muhtar, Umar Nasir; Onyibo, Leonard Ebube; Haladu, Mahmud Muhammad (FUDMA JOURNAL OF SCIENCES, 2025)
Kayan mata" are traditional herbal preparations used as aphrodisiacs by women in northern Nigeria. They are widely are widely consumed despite a lack of regulation, linked to socio-cultural factors and perceived benefits for female sexual enhancement. These preparations could poses potential health risks due to microbial contamination. This study aimed to assess the phytochemical profiles bacteriological quality, and antibiotic susceptibility patterns of bacterial isolates from "kayan mata" sold in Dutse, Jigawa State, Nigeria. Ten distinct samples were collected from five retail outlets, analyzed using standard methods for qualitative phytochemical screening, aerobic mesophilic bacterial counts AMBC), coliform counts, and isolation/identification of Escherichia coli, Pseudomonas aeruginosa, Salmonella spp., and Staphylococcus aureus. Antibiotic susceptibility was determined via Kirby-Bauer disk diffusion. Phytochemical screening revealed variable profiles, with alkaloids and terpenoids most common. Significant microbial contamination was found: 60% of the samples exceeded WHO limits for AMBC (ranging 3.5107.610 CFU/mL), and 40% had high coliform counts (7.210 CFU/mL). Microbial contamination included 50.0% each of E. coli and Salmonella spp, P. aeruginosa was 30.0%, but S. aureus was absent. High levels of antibiotic resistance were observed, particularly against Augmentin and most fluoroquinolones, with Salmonella isolates showing significant multidrug resistance (MDR). The isolates were most susceptible to Streptomycin and Trimethoprim-Sulfamethoxazole. Samples of "kayan mata" sold in Dutse had high levels of bacterial contamination, with some exhibiting multidrug resistance, which could pose significant public health risks. These findings highlight an urgent need for quality control, public education, and regulation of traditional herbal products.
Keywords: Antimicrobial Resistance (AMR); Public Health; Traditional Medicine; Microbial Contamination; Antibiotic Resistance